Many Questions Remain Unanswered About the Role of Microbial Transmission in Epizootic Shell Disease in American Lobsters (Homarus americanus) - Ishaq, Suzanne L.; Turner, Sarah M.; Tudor, M. Scarlett; MacRae, Jean D.; Hamlin, Heather; Kilchenmann, Joelle; Lee, Grace; Bouchard, Deborah (Frontiers in Microbiology, 2022)
Despite decades of research on lobster species’ biology, ecology, and microbiology, there are still unresolved questions about the microbial communities which associate in or on lobsters under healthy or diseased states, microbial acquisition, as well as microbial transmission between lobsters and between lobsters and their environment. There is an untapped opportunity for metagenomics, metatranscriptomics, and metabolomics to be added to the existing wealth of knowledge to more precisely track disease transmission, etiology, and host-microbe dynamics. Moreover, we need to gain this knowledge of wild lobster microbiomes before climate change alters environmental and host-microbial communities more than it likely already has, throwing a socioeconomically critical industry into disarray. As with so many animal species, the effects of climate change often manifests as changes in movement, and in this perspective piece, we consider the movement of the American lobster (Homarus americanus), Atlantic ocean currents, and the microorganisms associated with either.